Dietary fatty acids and edible fruit oil: potential therapy for heart - Abdul Kadir, Noor Atiqah Aizan; Azlan, Azrina (Universiti Putra Malaysia Press, 2017)
Cardiovascular disease (CVD) is a major cause of disability and premature death throughout the world. This disease is commonly experienced by people with unhealthy lifestyle, stress and physical inactivity. Cholesterol has received the most attention as single risk factor of CVD. Reducing the intake of cholesterol, saturated fat, and trans faty acids may be beneficial, yet controversy is still lingering to what constituents more beneficial dietary fats. The purpose of this article is to give an overview on the impact of major dietary fatty acids on cardiovascular morbidity and mortality and to give an insightful information regarding fatty acids composition in selected fruits oils in search for novel oils as potential therapy against CVD.